2017
DOI: 10.1021/acs.molpharmaceut.6b00969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Membrane PEGylation on Entry and Location of Antifungal Drug Itraconazole and Their Pharmacological Implications

Abstract: Itraconazole (ITZ) is an antifungal agent used clinically to treat mycotic infections. However, its therapeutic effects are limited by low solubility in aqueous media. Liposome-based delivery systems (LDS) have been proposed as a delivery mechanism for ITZ to alleviate this problem. Furthermore, PEGylation, the inclusion in the formulation of a protective "stealth sheath" of poly(ethylene glycol) around carrier particles, is widely used to increase circulation time in the bloodstream and hence efficacy. Togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 69 publications
5
27
0
Order By: Relevance
“…PEGylation modulates the effect of cholesterol on the conformation and dynamics of lipid bilayers [ 153 ]. Their simulations also captured the insertion of hydrophobic drug or light-sensitizing molecules (e.g., porphyrins, indocyanine green, itraconazole, and piroxicam) to the PEG layer and the hydrophobic region of the bilayer ( Figure 6 ) [ 154 , 155 , 156 , 157 , 158 ]. Recently, they simulated linear and branched PEG chains grafted on lipid bilayers, showing that the architecture and length of PEG–lipid conjugates influence the structure and dynamics of membranes, in agreement with experimental results [ 159 ].…”
Section: Pegylated Liposomesmentioning
confidence: 99%
“…PEGylation modulates the effect of cholesterol on the conformation and dynamics of lipid bilayers [ 153 ]. Their simulations also captured the insertion of hydrophobic drug or light-sensitizing molecules (e.g., porphyrins, indocyanine green, itraconazole, and piroxicam) to the PEG layer and the hydrophobic region of the bilayer ( Figure 6 ) [ 154 , 155 , 156 , 157 , 158 ]. Recently, they simulated linear and branched PEG chains grafted on lipid bilayers, showing that the architecture and length of PEG–lipid conjugates influence the structure and dynamics of membranes, in agreement with experimental results [ 159 ].…”
Section: Pegylated Liposomesmentioning
confidence: 99%
“…Advantages of PEG include the fact that it is non-fouling, well-tolerated by the body, can be obtained in a wide range of molecular weights and end-group chemistries and that it is FDA approved for a range of medical applications ( Hasan, 2017 ). There are many examples in which liposomes have been PEGylated, i.e., the PEG chains are incorporated within the lipid bilayer during synthesis (e.g., PEGlyated liposomes to incorporate itraconazole, antifungal agent, as well as dopamine-loaded PEGylated immunoliposomes; Kang et al, 2016 ; Dzieciuch-Rojek et al, 2017 ). Although effective, such a strategy is unsuitable for EV stabilization.…”
Section: A Bioengineering Approach To Manufacturing and Enhancing Ev mentioning
confidence: 99%
“…It has been demonstrated that PEG fragments not only increase the stability of NPs, but also reduce proteolysis, both of which result in increased circulation time and improved efficacy 20 .Since HA is a member of the mucopolysaccharide family with high viscosity that may attenuate protein release, we have also examined the protein releasing ability of the NPs (Fig. 1D).…”
Section: Characterization Of Npsmentioning
confidence: 99%